2022
DOI: 10.31083/j.jomh1806128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cardiovascular disease risk factors, health behavior and physical fitness according to visceral fat in older men

Abstract: Background: Obesity in older adults is increasing. The two types of fat involved in obesity are subcutaneous and visceral fat. We investigated the relationship between cardiovascular risk factors, health-related behaviors, and physical fitness based on the level of visceral fat in older men. Methods: Data from 1219 men aged ≥65 years who underwent health checkups at Korean hospitals from 2012 to 2020 were analyzed. Computed tomography (CT) data was used to divide participants into low visceral fat area (LVFA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Nonetheless, in a study investigating arteriosclerosis according to PA habits, similar to the results of the present study, it was reported that only aerobic activity was significant, and there was no significant difference regarding strength training [36]. Researchers also reported that <1 h of strength training per week could reduce the risk of MetS by 25% [37].…”
Section: Discussionsupporting
confidence: 84%
“…Nonetheless, in a study investigating arteriosclerosis according to PA habits, similar to the results of the present study, it was reported that only aerobic activity was significant, and there was no significant difference regarding strength training [36]. Researchers also reported that <1 h of strength training per week could reduce the risk of MetS by 25% [37].…”
Section: Discussionsupporting
confidence: 84%
“…The clinical characteristics of MHO in this study were similar to those reported previously. Lifestyle factors, including PA, play important roles in maintaining metabolic health and preventing obesity [25][26][27]. Conversely, an increased sedentary lifestyle increases the risk [28].…”
Section: Discussionmentioning
confidence: 99%